Productivity effects of land tenure systems in Sub-Saharan Africa - Place, Frank; Hazell, Peter B. R. (Wiley, 1993)
This article uses household survey data from Ghana, Kenya, and Rwanda to test if the indigenous land rights systems in sub‐Saharan Africa are a constraint on agricultural productivity. Rights which farmers hold over individual parcels of land vary widely, and are in many cases surprisingly privatized. Yet with few exceptions, land rights are not found to be a significant factor in determining investments in land improvements, use of inputs, access to credit, or the productivity of land. These results cast doubt on the need for ambitious land registration and titling programs at this time.